POAC Approach in Madrasa’s Principal Academic Supervision : Managerial Strategic to Enhance MAS Al-Zaytun Indonesia Teacher’s Competencies (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Effective academic supervision serves as a crucial managerial strategy for enhancing teacher competencies, encompassing pedagogical, professional, social, and personal dimensions. In the context of Islamic-based secondary education, the principal’s role is pivotal in ensuring that supervision is systematic, constructive, and oriented toward continuous improvement. This study aims to explore in depth how the POAC (Planning, Organizing, Actuating, and Controlling) management approach is implemented in the academic supervision practices of the principal of Madrasah Aliyah Swasta (MAS) Al-Zaytun Indonesia. Adopting a qualitative research design with a case study method, data were gathered through in-depth interviews, observation, and document analysis, then processed using Miles and Huberman’s interactive model of data reduction, data display, and conclusion drawing/verification. The findings indicate that the planning stage is conducted through structured needs assessments, SWOT analysis, and priority setting to align supervision with institutional goals. The organizing phase involves proportional task distribution and collaborative team formation, ensuring that supervisory responsibilities are clear and efficiently managed. The actuating phase emphasizes participatory engagement through dialogue-based coaching, peer collaboration, and formative feedback to foster reflective teaching practices. The controlling phase integrates structured monitoring tools, reflective evaluation sessions, and follow-up action plans to ensure continuous teacher development. The integrated application of the POAC framework not only enhances teacher performance but also strengthens the school’s capacity for quality assurance and sustainable improvement. Theoretically, this study contextualizes classical management principles in modern educational leadership. Practically, it offers a replicable framework adaptable to various educational settings, especially within the unique cultural and religious environment of Islamic secondary schools. This research underscores that systematic, collaborative, and reflective supervision can significantly contribute to holistic teacher competence and institutional advancement.